2016
DOI: 10.1021/acs.langmuir.6b01085
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning Directly Synthesized Porous TiO2 Nanofibers Modified by Graphitic Carbon Nitride Sheets for Enhanced Photocatalytic Degradation Activity under Solar Light Irradiation

Abstract: We report a direct approach to the fabrication of a composite made of porous TiO2 nanofibers (NFs) and graphitic carbon nitride (g-C3N4) sheets, by means of an angled two-nozzle electrospinning combined with calcination process. Different wt % amounts of g-C3N4 particles in a polymer solution from one nozzle and TiO2 precursors containing the same polymer solution from another nozzle were electrospun and deposited on the collector. Structural characterizations confirm a well-defined morphology of the TiO2/g-C3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…[20][21][22][23][24] The construction of heterojunctions by coupling of different semiconductors could not only enhance the utilization of sunlight, but also could create sufficient built-in potentials, which is beneficial for the separation of electronhole pairs for redox reactions. [25][26][27][28] The modification of BiVO 4 with g-C 3 N 4 has been reported, and the catalytic performance are improved compared with individual BiVO 4 .…”
mentioning
confidence: 99%
“…[20][21][22][23][24] The construction of heterojunctions by coupling of different semiconductors could not only enhance the utilization of sunlight, but also could create sufficient built-in potentials, which is beneficial for the separation of electronhole pairs for redox reactions. [25][26][27][28] The modification of BiVO 4 with g-C 3 N 4 has been reported, and the catalytic performance are improved compared with individual BiVO 4 .…”
mentioning
confidence: 99%
“…Combining carbon materials with photocatalysts has been considered as an effective approach to improve the separation of photo-generated electron-hole pairs,d ue to the low cost and high electrical conductivity of carbon. [18][19][20][21][22][23] Recent studies have indicated that partial substitution of carbon atoms by nitrogen atoms having electron lone pairs could significantly enhance the separation efficiency of electron-hole pairs by supplying additional negative chargei nt he carbon network. [24,25] However, uniformly coating N-doped Cl ayerso nh ollow micro-/nanoreactors to enhancet heir photocatalytic performance presentsaconsiderable challenge.…”
Section: Introductionmentioning
confidence: 99%
“…There are previous works about the fabrication of composite TiO 2 /g-C 3 N 4 fibers with electrospinning technique, following different experimental approaches (polymers, solvents, electrospinning parameters, light sources) and different g-C 3 N 4 /TiO 2 ratios [15,[17][18][19]. Comparing with the previous studies, the present work deals with: (a) The synthesis of g-C 3 N 4 /TiO 2 fibers with different ratios (up to 5 wt%) of g-C 3 N 4 and process conditions using PVP polymer, (b) all the reagents and precursors participated simultaneously to one-step electrospinning process, (c) a combination of solid-state and liquid phase characterization and analysis techniques for studying the catalysts properties and their photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%